Mathematical modeling of folate-related processes in human placenta - Dotsenko, V.A.; Obolenskaya, M.Yu. (Вiopolymers and Cell, 2014)
Aim. Description the folate-related processes in the human placenta using the stoichiometric model and investigation the system’s behavior under various conditions. Methods. The model is based on the stoichiometry of the reactions of the folate-related processes at steady state conditions and constructed using CellNetAnalyzer. Behavior of the system is described by elementary flux modes and control-effective fluxes depending on the activity of methylenetetrahydrofolate reductase and methionine synthase and input methionine flux. Results. Change in methylenetetrahydrofolate reductase activity causes a decrease in fluxes through the main routes of homocysteine elimination and increases the need for 5-methyltetrahydrofolate. Methionine synthase inactivation reduces 5-methyltetrahydrofolate consumption and increases the flux through the taurine syn-thesis. Lack of methionine leads to increased 5-methyltetrahydrofolate consumption, reduced homocysteine concentration and reduces the fluxes through the methionine cycle. Conclusions. Analysis of model functioning has shown the compliance of system’s functioning changes with the clinic parameters. There is evidence that the homocysteine level as a marker of folate-related processes functioning of is not sufficient to justify the therapy.